Pelatihan Pengembangan Bisnis Berbasis Syariah pada UMKM di Kelurahan Tamalanrea Jaya - Alimuddin Alimuddin; Muhammad Fauzan Garantjang; Fakhrul Indra Hermansyah; Haniek Khoirunnisa Baha; Nur Hazimah Alimuddin; Rezky Amalia Latif; Nur Ilmah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to provide micro, small, and medium-sized enterprises (MSMEs) in Tamalanrea Raya, Makassar, with an understanding of the importance of conducting business in accordance with Islamic principles. The training emphasizes aspects of fiqih muamalah, halal products, prohibited transactions and financing, as well as Islamic contract systems in business. The implementation method includes identifying target MSMEs, forming community groups, conducting training on Islamic business management, branding, and marketing strategies, and providing ongoing evaluation and mentoring. Through this program, MSMEs are expected to improve their understanding of halal and haram business practices, strengthen local community networks, and enhance economic sustainability in accordance with Shariavalues.